Pengembangan Video Pembelajaran Untuk Melatihkan Kreativitas Dan Inovasi Pada Materi Kegiatan Ekonomi Dan Jenis Pekerjaan Kelas IV SD - Putri, Sisilia Novilen Rahayu; Prasetya, Andreas Erwin; Rusmawan, Rusmawan (Universitas Negeri Malang, 2023)
This study aims to develop learning videos and determine the quality of the results of developing learning videos in social studies class IV SD. This research was conducted at SDN Bhaktikarya Condongcatur. This type of research is Research and Development (R&D) with the ADDIE model. Data collection techniques used are observation, interviews and questionnaires. The results of this study: 1) development of learning videos based on the ADDIE stages, namely analyze, design, develop, implement and evaluate, 2) The quality of learning videos obtained from validation results through 2 media experts and 2 material experts got a score of 4.53 entered into the category